2015
DOI: 10.1007/s11270-015-2689-7
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Biosolid Application on Soil and Native Plants in a Degraded Brazilian Atlantic Rainforest Soil

Abstract: We conducted a field experiment to determine whether application of biosolids (municipal sewage sludge) to degraded areas of the Brazilian Atlantic rainforest had the potential to contaminate native forest species with trace metals in the sandy soils of the region. Treatments consisted of 0, 2.5, 5, 10, 15, and 20 dry Mg biosolids ha −1 , with nine native pioneer, secondary, and climax tree species assessed for metal uptake: capixingui, aroeira-pimenteria, canafístula, cedro-rosa, mutamba, angico-vermelho, cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(16 citation statements)
references
References 11 publications
0
11
0
5
Order By: Relevance
“…In the next study, Liu et al [83] investigated the effects of laboratory-prepared MnOx NPs on the germination of lettuce ( L. sativa ) seeds in a water medium. MnOx NPs only slightly reduced the germination percentage from 84% (control) to 63% even at a high concentration of 50 mg L −1 and was not significantly different from that of the control.…”
Section: Nanomaterials Based On Essential Metals and Their Use In Agrmentioning
confidence: 99%
See 1 more Smart Citation
“…In the next study, Liu et al [83] investigated the effects of laboratory-prepared MnOx NPs on the germination of lettuce ( L. sativa ) seeds in a water medium. MnOx NPs only slightly reduced the germination percentage from 84% (control) to 63% even at a high concentration of 50 mg L −1 and was not significantly different from that of the control.…”
Section: Nanomaterials Based On Essential Metals and Their Use In Agrmentioning
confidence: 99%
“…Chloroplasts from leaves were isolated and analyzed for their level of photophosphorylation and oxygen evolutionMnNP-treated chloroplasts showed greater photophosphorylation, oxygen evolution with respect to control and MnSO4-treated chloroplasts. Positive effects on root and shoot elongation was observed[57] Lactuca sativa MnOx NPs 5–15 nm0.25, 0.5, 5, 10, mg L −1 Overall, the data suggests that MnOx NPs can be used as an Mn fertilizer (better than their soluble or bulk solid counterparts) for crop growth improvementMnOx NPs specifically improved the growth of lettuce seedlings by enhancing root elongation[83] …”
Section: Nanomaterials Based On Essential Metals and Their Use In Agrmentioning
confidence: 99%
“…Sewage sludge application is a beneficial alternative to recycle organic matter and nutrients as it improves soil physical, chemical, and biological properties, as well as improve vegetation establishment in degraded environments and assist the nutrition of agricultural crops (BORGES et al, 2009;LOBO et al, 2015;LU et al, 2012;SAMPAIO et al, 2016). However, before being used in agricultural crops and in addition to meeting the nutritional needs of plants and improving soil characteristics, sewage sludge needs to comply with the principles of environmental safety, with safe levels of heavy metals and offering no chemical or microbiological risk to human health or environment.…”
Section: Resultsmentioning
confidence: 99%
“…The canopy freeze-thaw effect could influence leaf physiology and further influence the canopy exchange fluxes of Ca and Mg in the early spring season. The dry deposition fluxes are mainly due to the greater interception of aerosols by the coniferous canopy, and the dry deposition that accumulates in the canopy during the dry (frozen) season is normally effectively washed at the beginning of rainfall episodes and is quickly exhausted 36,37 . The canopy exchange fluxes of K showed that the canopy leaches K in the spruce forest.…”
Section: Discussionmentioning
confidence: 99%